The Prevalence and Lived Experience of Pain in People Undertaking Dialysis - Ivy Moore; Pauline Byrne; Narelle Ilic; Jenny Heng-Chen Chen; Kelly Lambert (MDPI AG, 2023)
(1) Background: Pain is a prevalent and debilitating symptom associated with kidney failure. However, the impact of pain on quality of life remains unclear. We aimed to identify the prevalence, severity and characteristics of people undertaking dialysis impacted by pain and explore the lived experience of pain (2) Methods: A cross-sectional survey was administered to people undertaking haemodialysis or via telephone to those undertaking peritoneal and home haemodialysis in a single tertiary centre. Open-ended questions were analysed using thematic analysis. (3) Results: Responses were received from 131 participants (response rate 66.8%). Most were undergoing haemodialysis (87.0%). Pain was present in 92% (n = 121) of patients with 62% (n = 81) reporting pain as severe to excruciating. Common sites of pain were joints, muscle cramps, headaches, fistula pain, non-specific back pain and neuropathy. The overarching theme from the thematic analysis was that pain was a "debilitating and accepted burden" (4) Conclusions: Pain is highly prevalent, severe and debilitating in those on dialysis. There is a need for health care providers to be proactive and attentive to the management of pain. More research is needed to identify effective treatment approaches to decrease pain burden and improve the quality of life in those with kidney failure.